1981
DOI: 10.1038/290785a0
|View full text |Cite
|
Sign up to set email alerts
|

Sertoli–Leydig cell communication via an LHRH-like factor

Abstract: The primary function of the testosterone secreted by Leydig cells is the maintenance of spermatogenesis and hence fertility. This action of testosterone is mediated by the Sertoli cells which nourish and support the developing spermatozoa. As normal Sertoli cell function is so critically dependent on normal Leydig cell function, a regulatory influence of the Sertoli cells on the Leydig cells has been suggested. Indeed, follicle-stimulating hormone (FSH), which acts only on Sertoli cells, can also cause profoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

1982
1982
1993
1993

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 203 publications
(56 citation statements)
references
References 28 publications
1
55
0
Order By: Relevance
“…This aggregation effect will be less pronounced in the perfused tissue used in the present study as space left after shrinkage of the seminiferous epithelium is partly accounted for by the dilated lymphatics. Kerr, Rich & de Kretser (1979) have confirmed the impressions of earlier workers (Hanes, 1911;Lynch & Scott, 1951) (Chemes, Ri varóla & Bergada, 1976;Christensen & Peacock, 1980 (Schanbacher, 1979a;1980 (Schanbacher, 1979b;D'Occhio, Schanbacher & Kinder, 1982 (Catt et al, 1980) and an LHRH-like factor produced by the seminiferous tubule (Sharpe, Fraser, Cooper & Rommerts, 1981) have been shown to exert an intratesticular control of Leydig cell steroidogenesis, the relationship between these substances and Leydig cell structure and function has not yet been investigated. The role of the seminiferous epithelium in exerting some control of Leydig cell activity has been emphasized by Ucci (1982), who showed that there was an inverse relationship between Leydig cell size and activity, and germ cell maturation in the normal urodele testis.…”
Section: Morphometrysupporting
confidence: 71%
“…This aggregation effect will be less pronounced in the perfused tissue used in the present study as space left after shrinkage of the seminiferous epithelium is partly accounted for by the dilated lymphatics. Kerr, Rich & de Kretser (1979) have confirmed the impressions of earlier workers (Hanes, 1911;Lynch & Scott, 1951) (Chemes, Ri varóla & Bergada, 1976;Christensen & Peacock, 1980 (Schanbacher, 1979a;1980 (Schanbacher, 1979b;D'Occhio, Schanbacher & Kinder, 1982 (Catt et al, 1980) and an LHRH-like factor produced by the seminiferous tubule (Sharpe, Fraser, Cooper & Rommerts, 1981) have been shown to exert an intratesticular control of Leydig cell steroidogenesis, the relationship between these substances and Leydig cell structure and function has not yet been investigated. The role of the seminiferous epithelium in exerting some control of Leydig cell activity has been emphasized by Ucci (1982), who showed that there was an inverse relationship between Leydig cell size and activity, and germ cell maturation in the normal urodele testis.…”
Section: Morphometrysupporting
confidence: 71%
“…Sharpe & Fraser, 1980b) and in most respects these receptors are identical to LHRH receptors on the anterior pituitary (Clayton & Catt, 1981). Low levels of LHRH-like activity have been demonstrated in extracts of whole testis, seminiferous tubules and spent media from Sertoli cell cultures using a variety of assay techniques (Dutlow & Millar, 1981;Sharpe, Fraser, Cooper & Rommerts, 1981;reviewed by Sharpe & Harmar, 1983) and activity has also been demonstrated in vivo in testicular interstitial fluid from hCG-treated rats (Sharpe & Fraser, 1980a;. However, there is no definitive evidence that the Sertoli cell is the only or even the most important source of 'LHRH' within the testis, and attempts to purify this compound have made poor progress (Sharpe & Harmar, 1983).…”
Section: Seminiferous Tubule-leydig Cell Interactionmentioning
confidence: 99%
“…This concept received further support from the demonstration of receptor sites for GnRH on the Leydig cell (Sharpe & Fraser, 1980a). The stimulation of a GnRH-like factor by the testes after administration of hCG indicated that high doses of GnRH and its agonists might mimic the action of a naturally produced intra-gonadal regulator, the normal function of which was to reduce the responsiveness of the Leydig cells (Sharpe & Fraser, 1980b;Sharpe, Fraser, Cooper & Rommerts, 1981;Sharpe, 1982 (Fraser, 1980a).…”
Section: Gnrh Agonistsmentioning
confidence: 98%